A comparative study between single incision multiport laparoscopic appendicectomy and conventional laparoscopic appendicectomy in tertiary care hospital, Kanchipuram District, Tamil Nadu, India - K., Dhinesh Babu; S., Sujith Kumar (International Surgery Journal, 2017)
Background: To compare the outcome of single incision multiport laparoscopic appendectomy versus conventional laparoscopic appendicectomy in terms of patient recovery time, post-operative pain in Karpaga Vinayaga Medical College and Hospital, Kanchipuram District, Tamil Nadu, India. Methods: A randomized control study was done by alternation with sample size of 50 which divided into two groups (study group 25 and control group 25) and study period is from August 2012 to September 2014. Results: Patient in single incision laparoscopy group show less post-operative pain in the first 6 and 12 hours compared to the conventional laparoscopy group, but no difference was noticed between the two groups after 24 hours. No significant difference in operating times was noted between the procedures. Conclusions: One patient in 25 who underwent single incision laparoscopy had wound infection, but no wound complications were noted in the conventional appendicectomy group. Patients underwent Single incision laparoscopy are happier with scar when compared with conventional laparoscopy group. No difference noted in the duration of post-operative hospital stay.